Security Analysis for the Rio Quantum Network - Ribeiro, Mario C.; Vallejos, Raul O.; Temporão, Guilherme; Khoury, Antônio Z.; de Melo, Fernando (Anais do Workshop de Redes Quânticas (WQuNets), 2025)
The Rio Quantum Network (RQN) is a multi-user quantum communication network connecting several research institutions across the city of Rio de Janeiro. Capitalizing on its ring topology, the network implements a Sagnac-based variant of Twin-Field Quantum Key Distribution (TF-QKD)—a protocol that falls under the broader class of Measurement-Device Independent QKD (MDI-QKD). This design eliminates the need to trust the measurement devices, enhancing security against potential vulnerabilities. In the RQN, instead of each user operating a quantum light source in their lab, they perform phase and amplitude modulations on signals distributed by a central node. In this contribution, we employ the security framework of TF-QKD to estimate the secret key rate, ensuring rigorous performance evaluation under realistic conditions.